12-41=3(x-2)-8

Simple and best practice solution for 12-41=3(x-2)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-41=3(x-2)-8 equation:


Simplifying
12 + -41 = 3(x + -2) + -8

Combine like terms: 12 + -41 = -29
-29 = 3(x + -2) + -8

Reorder the terms:
-29 = 3(-2 + x) + -8
-29 = (-2 * 3 + x * 3) + -8
-29 = (-6 + 3x) + -8

Reorder the terms:
-29 = -6 + -8 + 3x

Combine like terms: -6 + -8 = -14
-29 = -14 + 3x

Solving
-29 = -14 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-29 + -3x = -14 + 3x + -3x

Combine like terms: 3x + -3x = 0
-29 + -3x = -14 + 0
-29 + -3x = -14

Add '29' to each side of the equation.
-29 + 29 + -3x = -14 + 29

Combine like terms: -29 + 29 = 0
0 + -3x = -14 + 29
-3x = -14 + 29

Combine like terms: -14 + 29 = 15
-3x = 15

Divide each side by '-3'.
x = -5

Simplifying
x = -5

See similar equations:

| 5x-7+8x= | | 45x^4-125=0 | | 6p-17=-33+2p | | 23=4-3n | | (3y-15)(y^2+4y-12)=0 | | 5-6x+9x=-15+5 | | 7+3r+9+6r= | | 9=-6(5)+b | | 25x^2+10x+4=0 | | g+7g= | | 82=5x | | x+45=2x-25 | | -2(-7-5b)= | | 8+7-4r-9r= | | 4*a+b=906.25 | | 7x^4+66x^2-40=0 | | 2x^2-3x+5=5 | | 10m=13 | | v-8=u | | 3s-18=24+9s | | 2r-25=-34+3r | | 7x^4+62x^2-9=0 | | 3y-7=-3y+-9 | | 81x^2+484=8 | | 4(x+3)=7x+15 | | X+7.5=-8 | | 7(3n+7(n+k)+2k)= | | V*2=80 | | 5+5b=2.5b | | y=(c-k)x+1 | | X+7.5=8 | | x^4+2x^2-80=0 |

Equations solver categories